Estimating the visitor’s willingness to pay towards biodiversity conservation at Kuala Lumpur Forest Eco Park, Malaysia, using the Contingent Valuation Method - FAZILAH MUSA; INTAN NURSUHADA MOHD SHAHRUDIN (Society for Indonesian Biodiversity, 2023)
Abstract. Musa F, Shahrudin INM. 2023. Estimating the visitor’s willingness to pay towards biodiversity conservation at Kuala Lumpur Forest Eco Park, Malaysia, using the Contingent Valuation Method. Biodiversitas 24: 3690-3699. The Kuala Lumpur Forest Eco Park is within the Bukit Nanas Forest Reserve, Malaysia's oldest and most biodiverse hill dipterocarp forest. The destruction of urban greenery in the heart of Kuala Lumpur has prompted stakeholders to conserve this forest as urban ecotourism areas for recreational, educational, and research activities. Due to the absence of a market, the economic value of biodiversity cannot be quantified in monetary terms from an economic perspective. Therefore, it will be difficult for stakeholders to justify the cost of conservation in their management in the future. This study's objective was to determine the economic value of biodiversity conservation at Kuala Lumpur Forest Eco Park by determining a visitor's Willingness to Pay (WTP) using the Contingent Valuation Method (CVM). A total of 250 questionnaires were distributed randomly to both international and domestic tourists to conduct this study. Five bid prices were chosen for domestic and international visitors based on the Logit Model's estimation of the visitor's WTP for biodiversity conservation. This study indicates that most visitors are willing to pay for biodiversity conservation influenced by religion, marital status, income, employment, and education. Furthermore, the results indicate that the WTP's mean and median per visit are MYR3.81 and MYR2.58 based on domestic visitor data. Consequently, this research may aid decision-makers in managing the financial strategy for biodiversity conservation activities. Thus, the conservation fee that visitors can accept based on their willingness to pay will further boost visitors' future visits to the Kuala Lumpur Forest Eco Park.